A new species of the genus Raphidopus Stimpson, 1858 (Crustacea: Decapoda: Anomura: Porcellanidae) from Peninsular Malaysia, with additional records of R. johnsoni Ng & Nakasone, 1994 from Southeast Asia, and a key to species in the genus - Osawa, Masayuki; Ng, Peter K. L. (Zootaxa, 2018)
A new species of the porcellanid genus Raphidopus Stimpson, 1858, is described on the basis of specimens from Penang and Kuala Selangor, Peninsular Malaysia. Raphidopus brevipes n. sp. is distinguished from its allied congeners, R. indicus Henderson, 1893 and R. johnsoni Ng & Nakasone, 1994, by the proportionally narrower carapace and stouter ambulatory legs, as well as the different dentition on the cutting edge of the dactylus of the larger cheliped. Raphidopus johnsoni, previously known only by the holotype from Singapore, is now also recorded from Phuket (Thailand) and Java (Indonesia). Raphidopus indicus and R. johnsoni are rediagnosed on the basis of the respective type material and other specimens. A key to species of the genus Raphidopus is provided.